If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(v + -4) + -6v = 0 Reorder the terms: 4(-4 + v) + -6v = 0 (-4 * 4 + v * 4) + -6v = 0 (-16 + 4v) + -6v = 0 Combine like terms: 4v + -6v = -2v -16 + -2v = 0 Solving -16 + -2v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -2v = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -2v = 0 + 16 -2v = 0 + 16 Combine like terms: 0 + 16 = 16 -2v = 16 Divide each side by '-2'. v = -8 Simplifying v = -8
| 23(m+27)=644 | | yi+y^2sinx=0 | | X(1)+y(2)=34 | | 7=43-k | | 160-2= | | y(y+13)=0 | | -54x-6+-37x+2=360 | | 5=(4x-8y) | | 5=4x-8y | | 5y-3+y+39=7y+40-5y | | 2a-14+a+23=b | | y^4-36y^2+1.024=0 | | 5(4x-8y)= | | 5+(n+4)=14 | | x*8=18 | | 9+5y-6=8y+6-2y | | 3(b+2)+b=3(b-2)-2 | | C/10-100=200 | | -3(-t+8-3)=-12 | | 2a-14=b | | 2q+54=-346 | | -7x+2=-14.8 | | 9=2u+1 | | -3(10-s+1)=-21 | | y-14.65/-1=-2.78 | | 3(x+4)+7=12 | | -(s+6)=18 | | (x-3)(x+4)-(5x-1)(x+7)= | | 3+(2+n)=9 | | 3p-28=p | | 1.7=3.9-r | | 8x+4=4x-5 |